The Urgency of Renewing Islamic Sufism (Neo-Sufism) Fazlur Rahman's Perspective in the Discourse of Modernity - Encung; Baiq Rida Kartini (AL-IKHSAN: Interdisciplinary Journal of Islamic Studies, 2023)
Problems between modern life and Sufism concepts that tend to be extreme. is still a hot topic because it is always discussed in various scientific disciplines. To answer this problem, Fazlur Rahman with his concept of Neo-Sufism explains how this concept is understood and the researcher wants to write down how to practice the Sufi lifestyle in the midst of modernity from the perspective of the figure in question. In this study the authors used a qualitative approach which was classified into library research using descriptive data analysis. From this method, researchers process and analyze to obtain data. Based on the research results obtained, Fazlur Rahman's Neo-Sufism is an attempt at socio-moral reconstruction of Muslims or in short the concept of Sufism which is based on three basic principles, namely: Referring to the normativity of the Qur'an and Sunnah, making the Prophet and the salaf as- Sholihin as a role model in its application, is principled in the attitude of tawazun in Islam (inner religious appreciation that wants to live an active life and be involved in social practice). Fazlur Rahman said that what we need to do at this point in practicing the Sufi lifestyle is to strengthen our faith, in accordance with the principles of the Islamic creed, the same evaluation of worldly life and spiritual life, continuing to participate in political activities, using property according to with moral and social needs and improve morale through dhikr and muroqobah techniques.